2020
DOI: 10.1155/2020/6489396
|View full text |Cite
|
Sign up to set email alerts
|

Human Supernumerary Teeth-Derived Apical Papillary Stem Cells Possess Preferable Characteristics and Efficacy on Hepatic Fibrosis in Mice

Abstract: Dental tissue has been acknowledged as an advantaged source for high-quality dental pulp stem cell (DPSC) preparation. However, despite the accomplishment of the separation of DPSCs from permanent teeth and supernumerary teeth, the deficiency of rigorous and systematic clarification on the signatures and efficacy will hinder their prospects in regenerative medicine. In this study, we primitively isolated permanent teeth-derived DPSCs and supernumerary teeth-derived apical papillary stem cells (SCAP-Ss) with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…We and other investigators have verified the dominant role of MSCs in multiple physiological and pathological microenvironments, together with clinical and preclinical applications in regenerative medicine such as osteoarthritis [ 4 ], aplastic anemia [ 5 , 6 ], Crohn’s disease [ 7 ], immune thrombocytopenia [ 8 ], fulminant hepatic failure [ 9 ], acute myocardial infarction (AMI) [ 10 ], graft-versus-host disease (GVHD) [ 11 ] and even the current corona virus disease 2019 (COVID-19) [ 12 ] through direct- and trans-differentiation, autocrine and paracrine, targeting immune-regulating cells and repairing damaged tissues. Since the 1960s, MSCs have been successfully isolated and identified from extensive sources including adult tissues (bone marrow, dental pulp, adipose and liver tissue) and perinatal tissues (placenta, umbilical cord, amniotic fluid and membrane) [ 13 – 16 ]. Among them, the bone marrow-derived BM-MSCs and umbilical cord-derived UC-MSCs are most recognized with the multiple applications and long-term proliferation properties, respectively [ 5 , 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We and other investigators have verified the dominant role of MSCs in multiple physiological and pathological microenvironments, together with clinical and preclinical applications in regenerative medicine such as osteoarthritis [ 4 ], aplastic anemia [ 5 , 6 ], Crohn’s disease [ 7 ], immune thrombocytopenia [ 8 ], fulminant hepatic failure [ 9 ], acute myocardial infarction (AMI) [ 10 ], graft-versus-host disease (GVHD) [ 11 ] and even the current corona virus disease 2019 (COVID-19) [ 12 ] through direct- and trans-differentiation, autocrine and paracrine, targeting immune-regulating cells and repairing damaged tissues. Since the 1960s, MSCs have been successfully isolated and identified from extensive sources including adult tissues (bone marrow, dental pulp, adipose and liver tissue) and perinatal tissues (placenta, umbilical cord, amniotic fluid and membrane) [ 13 – 16 ]. Among them, the bone marrow-derived BM-MSCs and umbilical cord-derived UC-MSCs are most recognized with the multiple applications and long-term proliferation properties, respectively [ 5 , 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For decades, we and other investigators have reported the establishment of MSCs from a various range of adult tissues such as bone marrow, adipose tissue, dental pulp and even human pluripotent stem cells (hPSCs). 2,[4][5][6] Differ from the adult tissue-derived counterparts, MSCs extracted from perinatal tissues (eg, umbilical cord, placenta) have been proved with preferable characteristics in multifaceted signatures such as juvenility and easy preparation without acquired pollution or ethical risk, and in particular, the hUC-MSCs with vigorously long-term reproductive capacity and better cellular pharmaceutical prospects. 2 Simultaneously, there is a suspicious attitude towards the therapeutic effect and variability in quality in considering the allogeneic cell sources and the probability of genetic variability.…”
Section: Introductionmentioning
confidence: 99%
“…H2030 (a human non‐small cell lung cancer cells), NB4 (a human acute promyelocytic leukemia cell line), and K562 (a human chronic myeloid leukemia cell line) were cultured in RPMI‐1640 basic medium (Gibco) containing 10% FBS, 1% NEAA (Gibco), 1% l ‐glutamine (Gibco), and 1% Penicillin and streptomycin (ThermoFisher) at 37°C and 5% CO 2 . HT29, hUC‐MSCs, and NB4 were passaged every 3–4 days with 0.05% Trypsin/EDTA (Gibco) at 37°C for 3–5 min and resuspended by the cell culture medium, as previously described (Wang et al, 2020; Yao et al, 2020; Zhang et al, 2017; Zhang, Wang, et al, 2018; Zhao et al, 2019). All the cell lines were conserved in our laboratory.…”
Section: Methodsmentioning
confidence: 99%